Federico García Lorca: sus negros y quemados como símbolos de represión - Ballesteros Dorado, Ana Isabel (2025)
The color black, within the extensive body of studies on Federico García Lorca, has typically been analyzed as a visual element in the poet's palette and in its figurative sense associated with night, death, mourning, grief, or evil, with few variations. This paper undertakes a thorough examination of how this color acquires a different significant nuance, one whose foundation can already be found in his early works. Recognizing this nuance and its connections with what is “burnt” provides an additional key to better understanding the avant-garde works of this author.